The Evolution of Islam Nusantara: Tracing the Origins and Examining Contemporary Manifestations of Pluralism and Tolerance - Gustiana Isya Marjani (International Journal of Nusantara Islam, 2023)
The primary objective of this study is to undertake a comprehensive and in-depth examination and analysis of the discourse surrounding Islam Nusantara, considering the evolutionary trajectory of ideas introduced by Gus Dur concerning the indigenization of Islam, spanning from the 1980s to the present-day concept of Islam Nusantara promoted by PBNU. As a result, the study endeavors to achieve a profound understanding and knowledge of the Nusantara Islamic civilization, which places utmost value on pluralism, tolerance, and the principle of rahmatan lil alamin, embodying compassion for all of creation. The research methodology employed in this study entails a rigorous review of relevant literature, drawing on diverse scholarly works exploring Islam Nusantara and tracing the origins of these ideas. Particular emphasis is placed on analyzing Gus Dur’s perspectives regarding the indigenization of Islam. The study’s findings reveal a significant correlation between the ideas espoused by Gus Dur and several noteworthy phenomena observed in contemporary Indonesian Islam. Firstly, a prevalent misinterpretation of jihad exists within specific segments of the Muslim community, leading to the emergence of explicit terrorist movements, such as ISIS and its sympathizers in Indonesia. Secondly, ongoing violations of religious freedom and beliefs continue to persist within the country. Thirdly, there is an expanding range of religious narratives and discourses prevalent in society that tend to lean towards radicalism and exhibit an aversion to diversity. Consequently, this study substantiates the notion that Islam Nusantara holds the potential to serve as a solid foundation for constructing a framework of religious moderation, serving as a crucial response to the progressively pervasive discourse and practice of religious radicalism within society